Friction reduction using self-waxing alpine skis - Styring, P.; Routh, A. F.; Parkinson, S. (Sports Engineering, 2012)
A continuously waxed ski has been developed that releases a thin film of lubricant under the base of a ski. This replicates the melt water layer observed in snow skis which is caused by frictional and solar heating. The system is particularly effective on artificial (dry) slopes where skiers slide on plastic bristles rather than snow. Speeds comparable to those achieved on snow are achieved using this system and this improves the experience for the skier. Speed enhancements on plastic slopes of up to 50 % have been achieved using solutions of polyethylene glycol in water. There is speed enhancement of approximately 9 % on artificial snow and 2 % on fresh alpine snow. The latter value is highly significant as it can be the difference between winning a medal in ski competitions and finishing outside the top ten. In addition to the quantitative data, qualitative athlete perceptions were also recorded and show that a feel like snow can be achieved on artificial surfaces. Because the lubrication system is attached to the ski, it allows personal performance enhancement irrespective of a water misting system being in operation or not. The design complies with the equipment regulations of the skiing`s international governing body so it can be used in competition.